Kreatifitas Tutor Bimago Magetan Dalam Pembelajaran Bahasa Arab Aktif (Maharatul Kitabah) Melalui Imla’ - Supriyanti, Iin (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Pondok Modern Gontor applies a test system for prospective students. Imla' is one of the materials tested as a requirement to enter Gontor. Imla' is a method of learning to write Arabic, which is a branch of Arabic science in which it learns the procedures and rules for writing good and correct Arabic. In studying Imla', of course, a teacher or tutor who understands the rules of writing Arabic is needed. One of the tutoring institutions that is sensitive to the needs of prospective Gontor students is BIMAGO Magetan. BIMAGO Magetan includes Imla' material in its teaching materials, with the aim of providing insight to prospective Gontor students regarding Maharah Kitabah. Active Arabic learning is one of the superior materials at BIMAGO Magetan, considering the lack of understanding of prospective students regarding the rules for writing good and correct Arabic. In implementing active Arabic learning (Maharah Kitabah) through Imla', the creativity of a tutor is required. It is undeniable that the creativity of a tutor can increase students' learning motivation. The approach that will be used by researchers in conducting this research is a qualitative research approach that is carried out directly in the field. In this descriptive qualitative research, the data collected came from observations, interviews and the results of documentation in the field. The object of this study were 15 informants, consisting of Imla' teaching tutors, students of BIMAGO Magetan, heads of BIMAGO Magetan and prospective walisantri. The results of this study show that there are 4 creative tutors in active Arabic learning (Maharah Kitabah) through Imla', namely: (1) Conducting Zoning Tutors, (2) Using Puzzle Media, (3) Using the WA Application Video Call Feature, and (4) Create Short Videos.